Investigating Undergraduate Students' Strategies in Reading Comprehension (A Case Study of the English Education Department at Wiralodra University) - wati, Atikah; Efendi, Nasori; Anggrarini, Natalia; Nurhayati, Titin (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
As one of the language skills, students tend to have difficulties in reading as one of the language skills, especially difficulties in comprehending the text. Because of that, this research aims to investigate undergraduate students' strategies in reading comprehension, which focus on global reading strategy (GLOB), problem-solving strategy (PROB), and support reading strategy (SUP) adapted from Mokhtari & Sheorey (2002). This research was conducted using qualitative research with a case study design. A close-ended questionnaire and semi-structured interview were used as the instruments of this research to gain information about students' reading strategies in reading comprehension, especially in academic reading subjects. Twenty students from the fourth semester of one University in Indramayu participated in this research. The finding shows that the students use PROB with 80,62%, followed by GLOB at 77,38%, and SUP at 73,11%. Students stated in the interview that PROB was helpful and made them focus on understanding information from difficult text. In GLOB, the students usually guess the text content and check whether their guessing related to the text is correct or incorrect. While in SUP, the students circled the text and went back and forth to find the relationship among ideas in the text. Eventually, the findings can be useful for those who wish to conduct a study on students' reading strategies. The further researcher can provide tests to determine the student's ability in reading comprehension to obtain the complete data.